#TITLE_ALTERNATIVE# - ANISA KURNIA (NIM: 25313314), LUTHFIDA
Manufacturing industry has the high potential level of fatigue at workers due to environmental condition do not eligible, the workload is uncertain, and the potential for sleep disturbance as a result of the implementation of shiftwork, that causing an increase in the number of occupational accidents. Fatigue plays a role in the occurrence of accidents due to fatigue lowers a person's ability to process information and respond to the dangers of hazardous conditions occurring. Therefore, the research aims to identify the influence of environmental work factors, workload, and sleep quality exposure to fatigue on perceived by workers at PT. X. Environmental work assessment is done by 4 in 1 environment. While the workload and sleep quality were measured with NASA-TLX and PSQI. The sample size of this study is 123 workers. The measurement results show that the average intensity of noise and WBGT do not exceed TWA. While the lighting intensity measurement results show that the indoor area still does not meet the TWA between 190.67 to 285 lux. The average score of job demand, manager support, and change had lower than other dimensions of work-related stress for all work locations. The mean score of NASA-TLX workload ranged from 61.05 to 74.78. A total of 88.62% of the workers of PT. X had poor sleep quality. PT. X workers had high workload and poor sleep quality, but more than 50% workers did not experience fatigue that shown by the decreased value of reaction time and blood pressure after work. It was caused by 70% workers had normal blood pressure and 90% workers aged ≤40 years so the lower risk of being fatigue, PT. X also had implemented administrative control i.e. work hours management and short-term shift rotation system, workplace of PT. X workers was comfortable with room temperature between 20oC-26oC, adequate lighting intensity, and low noise exposure, and workers was allowed to napping in the workplace. Logistic regression analysis showed that workload, noise, and shiftwork affect fatigue based on systolic blood pressure measurement. As for the reaction time and diastolic blood pressure, the significant level was larger than 0.05 which means that fatigue based on reaction time measurement did not affect by job tenure and noise exposure and fatigue based on diastolic blood pressure measurement did not affect by age.